Orthodontic considerations for managing patients with functional movement disorders: a narrative review and clinical guide - Al-Jewair, Thikriat; Zylalaj, Ajola; Poursattar Bejehmir, Arash (Frontiers in Dental Medicine, 2025)
BackgroundFunctional Movement Disorder (FMD) is a neurological condition involving involuntary movements without structural brain or nerve damage. It can significantly affect the craniofacial region, disrupting facial and oral motor functions and complicating dental and orthodontic care. This narrative review outlines the clinical presentation of FMD, emphasizing its relevance in orthodontics and offering a clinical management guide.FindingsA systematic approach is proposed, detailing strategies from the initial screening visit through active treatment, retention, and post-retention stages. Key strategies include using fixed appliances for better control, scheduling shorter visits to reduce symptom aggravation, and incorporating distraction techniques. Collaborative care with neurologists, psychiatrists, psychologists, physical therapists, and dental professionals is vital, addressing both motor and psychological factors.Conclusion and relevanceSpecialized training, improved diagnostic methods, and customized treatment plans are crucial for managing FMD in orthodontics. These efforts are necessary to optimize care and outcomes for affected patients.